Transitions of young migrants to initial vocational education and training in Germany : the significance of social origin and gender - Beicht, Ursula [Verfasser]; Walden, Günter [Verfasser] (My University, 2017)
"The topic of the present paper is how successful young people from a migration background in Germany are in making the transition to initial vocational education and training (VET). Particular emphasis is placed on interactions with social origin and gender. The analyses are based on the 2011 BIBB Transitional Study, a representative survey of over 5000 young people living in Germany from the birth cohorts between 1987 and 1993. It is revealed that a migration background exerts a negative effect on the chances of progressing to company-based or fully qualifying training. For a successful transition to VET the school-leaving qualification achieved is very important and migrants often achieve only lower school-leaving qualifications. Interaction effects occur between migration background, social origin and gender. The transition chances of young migrants are, however, also worse when a multitude of relevant factors are controlled for. The results indicate that migrants in German society still have to contend with reservations." (authors' abstract; BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.5 Migranten; G 1.3.2.2 Übergänge; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; Jugendlicher; Migrant; Berufseinmündung; Ausbildungschance; Soziale Herkunft; Geschlechtsspezifische Faktoren; BIBB-Übergangsstudie; Ausländischer Jugendlicher